Minerological characterization studies of archaeological pottery sherds using FT – IR and TG A - DTA - S. Meyvel, R. Palanivel, (Recent Research in Science and Technology, 2009)
The Archaeological pottery sherds excavated in Alagankulam, an ancient port city of Tamilnadu, India, have historical significance owing to the heritage and trade link possessed with the Roman Empire. They were examined by employing the analytical techniques Fourier Transform Infra Red (FTIR) and Thermogravimetry – Differential Thermal Analysis (TGA-DTA) with an objective to identify the mineralogical characteristics of the raw materials used for their production. Based on the mineralogical assemblages observed in FTIR, the nature of the clay used, the textural and vitrification structures were inferred. The reactions associated with the mineral compositions present in the potsherds on controlled heating over the linear temperature ramp from room temperature to 1200°C in an inert atmosphere were realized by TGA-DTA results. The characterization studies were able to indicate the conditions of firing process adopted and firing temperature attained by the artisans at the time of manufacture of the artifacts of the present investigation.